Fitness, Gender, Körper: Materialisierungen evangelikaler Körpertheologien in den USA - Radermacher, Martin (Body Politics, 2015)
English abstract: Since the late 1950s, there is a body-related discourse in the United States which aims for a fit and healthy body – based on biblical principles. In tune with popular societal body and fitness ideals, this discourse of “devotional fitness” has gained popularity among evangelicals in the last decades. This field is suited to investigate how evangelical body theologies are materialized. In this article, I will look at this question, introducing both historical backgrounds and contemporary examples, and taking a criti-cal point of view with regard to the construction of gender ideals and gender roles. Devo-tional fitness programs situate popular ideals of physical perfection within a conservative evangelical worldview which understands the husband as head and bread-winner of the family, and the wife as potentially weak against the temptations of food. The article thus focuses on central motifs of North American body history in the 20th and 21st century.